تسبيب قرار التوقيف في التشريع الجزائي الأردني: دراسة مقارنة - المحاسنة، محمد أحمد علي (الجامعة الأردنية - عمادة البحث العلمي, 2015)
The Jordanian criminal procedures did not include provisions which is related to causation of detention decision, and the cases that justify the decision of detention, extension, and notify the defendant reasons for his detention with contrary of other criminal legislations such as French and Lebanese legislation This causes main problems in practically field, this study will discuss what is the extent of the commitment of the prosecutor or judge in causation of detention decision in the Jordanian criminal legislation. The researcher studies this subject, analyzes and defines the attitude of the legislator in France, Egypt, Lebanon, and Jordan from the causation of detention decision, and to indicate to the provisions of judiciary in France, Egypt, and Jordan, the researcher finds out that The Jordanian criminal of the procedures fall short in handling the idea of causation of detention decision, or extension, and the cases that justify the decision of detention, extension, and notifying the defendant reasons for his detention, so he suggests that the article(114), and article (116) of The Jordanian criminal procedures should be amend in order to bridge this gap to eliminate any difficulties and the defendant reasons for his detention that may arise by this subject.
جاء قانون أصول المحاكمات الجزائية الأردني خاليا من النص على وجوب تسبيب قرار التوقيف أو تمديده، وبيان الحالات التي تبرر اتخاذ قرار التوقيف أو التمديد، وتبليغ المشتكى عليه بأسباب توقيفه، خلافا لما نصت عليه بعض التشريعات الجزائية المقارنة، كالتشريع الفرنسي واللبناني، الأمر الذي يثير من الناحية العملية إشكالية رئيسية جاءت هذه الدراسة لمعالجتها، فما هو مدى التزام المدعي العام أو قاضي الحكم في تسبيب قرار التوقيف في التشريع الجزائي الأردني؟ وقد تناول الباحث هذا الموضوع بالدراسة والتحليل، وقام الباحث بتحديد موقف المشرع في كل من فرنسا ومصر ولبنان والأردن من تسبيب قرار التوقيف، مع الإشارة إلى أحكام القضاء الفرنسي والمصري والأردني المتعلقة بهذا الموضوع. وتوصل الباحث إلى أن قانون أصول المحاكمات الجزائية الأردني فيه نقص وقصور، فيما يتعلق بتسبيب قرار التوقيف أو تمديده، وبيان الحالات التي تبرر اتخاذ قرار التوقيف أو التمديد، وتبليغ المشتكي عليه بأسباب توقيفه، واقترح تعديل نص المادتين (114) و(116) من القانون نفسه لسد النقص ومعالجة أية صعوبات قد يثيرها هذا الموضوع.
Keywords: القوانين والتشريعات -- القانون الجزائى -- المحاكمات الجزائية -- القرارات التوقيفية -- حقوق الانسان -- الأردن